Penatalaksanaan Holistik Pasien Wanita dengan Dermatitis Seboroik Melalui Pendekatan Dokter Keluarga - Dinah Zhafira Qubro; Azelia Nusadewiarti (Majority, 2020)
Chronic skin diseases significantly affect the patient's quality of life, one of those diseases is seborrheic dermatitis. Seborrheic dermatitis affects 2-5% of the population, can affect infants in the first three months of life and adults aged 20-50 years. Data from the Riset Kesehatan Dasar Indonesia (2008) shows a dermatitis prevalence of 6.8%. Lampung Province is included in the top 10 provinces with the most prevalence of dermatitis. It takes the role of a family doctor who can manage patients holistically from various aspects of life. This study is a descriptive study of case report. Primary data were obtained through alloanamnesis, physical examination, and home visits. Secondary data were obtained from patient’s medical record. Patient Mrs. N, 41 years old, looks scaly on her scalp, yellowish in color, and smells with intense itching since the last 1 month. Complaints of itching worsen if the patient sweats. The patient had experienced the same symptoms 1 year ago. Patients often wash her hair to reduce the itching feeling and immediately wear the hijab when the hair is not completely dry. The patient likes to eat coconut milk. Pharmacologic and non-pharmacological interventions were carried out in the form of education about seborrheic dermatitis in patients and her families. The result of the evaluation of the intervention is an increasing the disease knowledge in patient and there is family involvement in the patient's treatment process.